Multi-model GWAS reveals genetic determinants of grain hardness, size and weight in bread wheat (Triticum aestivum L.) - Deepa Bhadana; Jitendra Kumar; Shoeb Ahmed; Anita Kumari; Monika Garg; Joy Roy; Rahul Kumar (Molecular Genetics and Genomics, 2026)

A robust 1K-core marker set for wild germplasm management and targeted pre-breeding of rice: development and applications - Debashree Dalai; Dipti Ranjan Pani; Swayamsiddha Aswita Dhal; Motilal Behera; Tapan Kumar Mondal; Muhammad Azaharudheen TP; Joshitha Vijayan; Deepa Sarkar; Pallavi Ghose; Abhijeet Roy; Kutubuddin A Molla; Anilkumar C; et al. (Theoretical and Applied Genetics, 2026)

A systems biology approach reveals dual neurotherapeutic mechanisms of Dioscorea bulbifera in Alzheimer’s disease via estrogen signaling and cholinergic modulation - Mayank Roy Chowdhury; Sudarshana Deepa Vijaykumar (Inflammopharmacology, 2025)

Exploring bioactive natural products for treating neurodegenerative diseases: a computational network medicine approach targeting the estrogen signaling pathway in amyotrophic lateral sclerosis and Parkinson’s disease - Mayank Roy Chowdhury; Ramireddy Venkata Sai Reddy; Navaneeth K. Nampoothiri; Rajeswara Reddy Erva; Sudarshana Deepa Vijaykumar (Metabolic Brain Disease, 2025)

Integrated systems pharmacology, molecular docking, and MD simulations investigation elucidating the therapeutic mechanisms of BHD in Alzheimer’s disease treatment - Mayank Roy Chowdhury; Karamveer Karamveer; Basant K Tiwary; Navaneeth K Nampoothiri; Rajeswara Reddy Erva; Vijaykumar Sudarshana Deepa (Metabolic Brain Disease, 2024)

Enriched Environment Contributes to the Recovery from Neurotoxin-Induced Parkinson’s Disease Pathology - Daphne Alcalá-Zúniga; Erika Espinoza-Torres; Ranjit Kumar Das; Magaly Vargas; Oscar Maldonado; Omar Benavides; Arvind Manojkumar; Roberto de la Garza; Natalia Davila; Isaac Perez; Alejandro Hernandez Martinez; Deepa Roy; et al. (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a neurological disorder that affects dopaminergic neurons. The lack of understanding of the underlying molecular mechanisms of PD pathology makes treating it a challenge. Several pieces of evidence support the protective role of enriched environment (EE) and exercise on dopaminergic neurons. The specific aspect(s) of neuroprotection after exposure to EE have not been identified. Therefore, we have investigated the protective role of EE on dopamine dysregulation and subsequent downregulation of DJ1 protein using in vitro and in vivo models of PD. Our study for the first time demonstrated that DJ1 expression has a direct correlation with dopamine downregulation in PD models and exposure to EE has a significant impact on improving the behavioral changes in PD mice. This research provides evidence that exercise in EE has a positive effect on PD without interfering with the current line of therapy.

Unraveling metabolic pathways and key genes in Alzheimer’s, type 2 diabetes, and estrogen dysregulation among aging women: a systems biology approach - Mayank Roy Chowdhury; Vinith Kumar; Vijaykumar Sudarshana Deepa (Journal of Proteins and Proteomics, 2024)

Cross-species transferability of IRAP retrotransposon markers and polymorphism in black pepper (Piper nigrum L.) - Manjushri Dinkar Dongare; Swapna Alex; K. B. Soni; K. P. Sindura; Deepa S. Nair; Roy Stephen; Elizabeth Jose (Genetic Resources and Crop Evolution, 2023)

Comparative analysis of VMT genes/proteins in selected plant species with emphasis on bread wheat (Triticum aestivum L.) - Hemant Sharma; Shayaba; Rahul Kumar; Jitendra Kumar; Deepa Bhadana; Ritu Batra; Rakhi Singh; Sachin Kumar; Joy K Roy; Harindra S. Balyan; Pushpendra K. Gupta (Genes & Genomics, 2023)

Effects of nodding broomrape parasitism on growth, physio-biochemical changes and yield loss of Withania somnifera (Linn.) Dunal plant - Kuldeepsingh A. Kalariya; Deepa Shahi; Parmeshwar Lal Saran; Ram Prasnna Meena; Narendra Gajbhiye; Prince Choyal; Satyajit Roy (Vegetos, 2023)

Geochemistry, mineralogy and nutrient concentrations of sediment of River Pampa in India during a massive flood event - Ajoy Saha; Sibina Mol Salim; Deepa Sudheesan; Vettath Raghavan Suresh; Subir Kumar Nag; Preetha Panikkar; Thankam Theresa Paul; Rani Palaniswamy; Basanta Kumar Das; Arnab Roy Chowdhury (Arabian Journal of Geosciences, 2020)

Climato-environmental influence on breeding phenology of native catfishes in River Ganga and modeling species response to climatic variability for their conservation - Uttam Kumar Sarkar; Malay Naskar; Pankaj Kumar Srivastava; Koushik Roy; Soma Das Sarkar; Sandipan Gupta; Arun Kumar Bose; Saurav Kumar Nandy; Vinod Kumar Verma; Deepa Sudheesan; Gunjan Karnatak (International Journal of Biometeorology, 2019)

Understanding the role of climatic and environmental variables in gonadal maturation and spawning periodicity of spotted snakehead, Channa punctata (Bloch, 1793) in a tropical floodplain wetland, India - Gunjan Karnatak; Uttam Kumar Sarkar; Malay Naskar; Koushik Roy; Sandipan Gupta; Saurav Kumar Nandy; Pankaj Kumar Srivastava; Soma Das Sarkar; Deepa Sudheesan; Arun Kumar Bose; Vinod Kumar Verma (Environmental Biology of Fishes, 2018)

Benchmarking pre-spawning fitness, climate preferendum of some catfishes from river Ganga and its proposed utility in climate research - Uttam Kumar Sarkar; Malay Naskar; Koushik Roy; Deepa Sudeeshan; Pankaj Srivastava; Sandipan Gupta; Arun Kumar Bose; Vinod Kumar Verma; Soma Das Sarkar; Gunjan Karnatak; Saurav Kumar Nandy (Environmental Monitoring and Assessment, 2017)

Immunoregulation of a CB2 Receptor Agonist in a Murine Model of NeuroAIDS - Santhi Gorantla; Edward Makarov; Deepa Roy; Jennifer Finke-Dwyer; L. Charles Murrin; Howard E. Gendelman; Larisa Poluektova (Journal of Neuroimmune Pharmacology, 2010)

Biodiversity of organotin resistant Pseudomonas from west coast of India - Upal Roy; Deepa Nair (Ecotoxicology, 2007)